Near-infrared-dye labeled tumor vascular-targeted dimer GEBP11 peptide for image-guided surgery in gastric cancer - Tian, Zuhong; Liang, Shuhui; Zhou, Xinmin; Luo, Hui; Tian, Miaomiao; Zhang, Xianghan; Guo, Changcun; Zhang, Jing (Frontiers in Oncology, 2022)
Introduction Positive resection margins occur in about 2.8%-8.2% gastric cancer surgeries and is associated with poor prognosis. Intraoperative guidance using Nearinfrared (NIR) fluorescence imaging is a promising technique for tumor detection and margin assessment. The goal of this study was to develop a tumor-specific probe for real-time intraoperative NIR fluorescence imaging guidance. Methods The tumor vascular homing peptide specific for gastric cancer, GEBP11, was conjugated with a near-infrared fluorophore, Cy5.5. The binding specificity of the GEBP11 probes to tumor vascular endothelial cells were confirmed by immunofluorescent staining. The ability of the probe to detect tumor lesions was evaluated in two xenograft models. An orthotopic gastric cancer xenograft model was used to evaluate the efficacy of the GEBP11 NIR probes in real-time surgical guidance. Results In vitro assay suggested that both mono and dimeric GEBP11 NIR probes could bind specifically to tumor vascular epithelial cells, with dimeric peptides showed better affinity. In tumor xenograft mice, live imaging suggested that comparing with free Cy5.5 probe, significantly stronger NIR signals could be detected at the tumor site at 24-48h after injection of mono or dimeric GEBP11 probes. Dimeric GEBP11 probe showed prolonged and stronger NIR signals than mono GEBP11 probe. Biodistribution assay suggested that GEBP11 NIR probes were enriched in gastric cancer xenografts. Using dimeric GEBP11 NIR probes in real-time surgery, the tumor margins and peritoneal metastases could be clearly visualized. Histological examination confirmed the complete resection of the tumor. Conclusion (GEBP11)2-ACP-Cy5.5 could be a potential useful probe for intraoperative florescence guidance in gastric cancer surgery.